Liberdade E Razão Pública: Uma Análise Normativa Do Caso Da Interrupção Voluntária Da Gravidez No Stf - Oliveira, Monica Conceicao Da Cunha [UNIFESP] (2018)
This Dissertation Aims At Investigating Three Decisions From The Brazilian Supreme Federal Court That Deal With Reproductive Rights And More Specifically Voluntary Interruption Of Pregnancy; And Also The Understanding About Women's Rights In Civil Society In The Light Of The Concepts Of Liberty, Privacy And Most Of All The Rawlsian Concept Of Public Reason.